Individual differences in the propensity to make attributions to prejudice. (February 2018) - Miller, Stuart S.; Saucier, Donald A.
Whether racism is perceived in ambiguous situations may depend on individual differences in perceivers' beliefs about the prevalence of racial prejudice and discrimination, trivialization of targets' concerns, and vigilance and confidence in recognizing instances of racial prejudice. In Studies 1 and 2, we develop a psychometrically sound measure of these beliefs, the Propensity to Make Attributions to Prejudice Scale (PMAPS), and provide evidence that the PMAPS is related to individual differences in the justification and suppression of prejudice. Studies 3 and 5 provide evidence that the PMAPS predicts attributions to prejudice in a variety of situations. Theoretically consistent racial and gender differences in the PMAPS were found in a large sample (Study 4). Together, these data provide evidence supporting the reliability and validity of the PMAPS and provide insights about the role that beliefs and expectations play in third-party observers' judgments about expressions of prejudice.